Crystal and molecular structure of Michler’s ketone as a pure phase - Shotonwa, Ibukun Oluwaseun; Boere, Rene Theodoor (European Journal of Chemistry, 2022)
The pure phase crystals of Michler’s ketone, [4-(CH3)2NC6H4]2CO, are reported herein as monoclinic in the space group P21/c with Z’ = 2 by single-crystal X-ray diffraction. The data collection of the title compound proved quite difficult, which could explain why the structure has not been reported previously. The crystallographically independent molecules in the asymmetric unit differ by dihedral angles of 24.60/30.34° and 25.25/27.20° between the essentially planar 4-dimethylaminophenyl (DMAP) rings and the central C2C=O plane of the ketone and dihedral angles of 52.14 and 47.41°, respectively, between the DMAP planes. A DMAP ring of each molecule overlaps in the lattice with a methyl ring that overlays the ring centroid of the opposite number (CMe-Cg distances of 3.452 and 3.505 Å), describing sets of trifurcated CAr-acceptor hydrogen bond interactions (HBIs). The trifurcated HBIs possess H∙∙∙CAr distances of 2.90, 2.75, and 2.86 Å; CMe∙∙∙Car distances of 3.554(5), 3.798(5) and 3.881(5) Å; and ÐCMe-H∙∙∙CAr of 115.0, 121.3 and 167.7°, respectively. Stabilization of the asymmetric unit in the title compound is further achieved by supramolecular synthons such as CMe-H∙∙∙CAr (2.831 Å), CAr-H∙∙∙O (2.561 Å) and CAr-H∙∙∙H-CAr (2.290 Å) and coulombic CMe-Ocontact (3.209 Å). The structures of the two independent molecules in the asymmetric unit of the title compound were compared with the same molecule as found in the following co-crystals, adducts or salts: a halogen-bonded adduct with 1,4-diiodotetrafluorobenzene; a hydrogen-bonded adduct with a fluorinated phenol; a coordination complex between the ketone and a trimeric mercury acceptor; and two salts from protonation or methylation at one of the amino nitrogen atoms.